A sign of the dayside current wedge in geomagnetic observations at Stará Ďala (present-day Hurbanovo) on 16 April 1938 - KOČI, Eduard; VALACH, Fridrich (Contributions to Geophysics and Geodesy, 2025)
The recently proposed dayside current wedge likely explains the mechanism behind the well-known Carrington geomagnetic storm on 2 September 1859, as well as an event observed in Europe on 29 October 2003. Both events were swift and intense, had unusually short recovery phases, and the most violent variation of the horizontal intensity within them occurred at mid-latitudes in the morning MLT (magnetic local time) sector. In this paper, we add the third event to the two mentioned above, a short-lasting intense mid-latitude geomagnetic field variation that occurred on 16 April 1938. We present the reconstructed magnetogram with magnetic declination recorded at Stará Ďala on 16 April 1938 and demonstrate that, at around 08:30 of MLT, the Stará Ďala Observatory was likely situated within the central part of the wedge. The time series of horizontal intensity and declination from Western Europe and North America are consistent with our hypothesis that the dayside current wedge played a role in the event of 16 April 1938.